HUMAN-CENTERED GOVERNANCE APPROACH IN THE APPLICATION OF LAYANAN TUNGGU DISDUKCAPIL PEKANBARU AS AN ONLINE PUBLIC SERVICE - Arya Luthfi; Zaili Rusli; Harapan Tua; Tantri Yazid (Sultan Syarif Kasim State Islamic University, Riau, 2024)
User experience (UX) plays an important role in digital public services. Poor user experience can cause confusion among the public and hamper the administrative process in public services. Pekanbaru City has online-based public services that can facilitate the public. However, the public service applications are not easy to use so public administration studies are still needed from a user experience (UX) perspective. The method used in this research is an exploratory qualitative approach using secondary data. The results show that the application owned by the Population and Civil Registration Agency of Pekanbaru City requires in-depth study and redesign so that the public goals can be achieved.